2016
DOI: 10.1177/0300985816653172
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Vesicular Stomatitis New Jersey Virus Infection in Deer Mice (Peromyscus maniculatus) Transmitted by Black Flies (Simulium vittatum)

Abstract: The natural transmission of vesicular stomatitis New Jersey virus (VSNJV), an arthropod-borne virus, is not completely understood. Rodents may have a role as reservoir or amplifying hosts. In this study, juvenile and nestling deer mice ( Peromyscus maniculatus) were exposed to VSNJV-infected black fly ( Simulium vittatum) bites followed by a second exposure to naive black flies on the nestling mice. Severe neurological signs were observed in some juvenile mice by 6 to 8 days postinoculation (DPI); viremia was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Outbreak viruses can overwinter with the same viral genotype re-emerging for a second-year outbreak [3,27], as occurred in 2004-2005, 2005-2006, 2014-1015, and in the most recent 2019-2020 outbreaks. Several hypotheses have been proposed to explain the maintenance of VSV during inter-epidemic periods, mainly by suggesting the presence of a yet to be identified, natural mammalian reservoir [28,29]. However, from a vector perspective, the vertical and venereal transmission of arboviruses are possible maintenance mechanisms during inter-epidemic periods in which the virus is maintained in a vector population independent of feeding on viremic animals [30].…”
Section: Discussionmentioning
confidence: 99%
“…Outbreak viruses can overwinter with the same viral genotype re-emerging for a second-year outbreak [3,27], as occurred in 2004-2005, 2005-2006, 2014-1015, and in the most recent 2019-2020 outbreaks. Several hypotheses have been proposed to explain the maintenance of VSV during inter-epidemic periods, mainly by suggesting the presence of a yet to be identified, natural mammalian reservoir [28,29]. However, from a vector perspective, the vertical and venereal transmission of arboviruses are possible maintenance mechanisms during inter-epidemic periods in which the virus is maintained in a vector population independent of feeding on viremic animals [30].…”
Section: Discussionmentioning
confidence: 99%
“…As with most arbovirus transmission cycles, vertebrate hosts typically act as amplifying reservoirs capable of producing sustained levels of viremia. Serological surveys have shown that species, such as bats, deer, and monkeys, living in endemic areas develop neutralizing antibodies against the virus [2,18,20], and that small grass-eating rodents, such as cotton rats [18,19] and deer mice [75,76], might play a role in viral maintenance. However, a definitive natural viremic host reservoir for VSV is yet to be identified [2].…”
Section: Vectors and Mechanisms Of Transmissionmentioning
confidence: 99%
“…The main natural host reservoir of Ebola virus is thought to be certain species of Old World fruit bats, but the virus is capable of transmission to many other mammalian species [1,[7][8][9][10]. The natural host reservoir of VSV is thought to be mainly small rodents, such as deer mice, with sandflies acting as transmission vectors; however, VSV is also capable of infecting many other animal species and can be transmitted via other insects [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. a Pool feeders, i.e., hematophagous arthropods that lacerate their host's blood vessels and then consume the pooled blood.…”
Section: Introductionmentioning
confidence: 99%
“…); however, mosquitoes (which are 'capillary vessel feeders') may also be involved [15,19,[22][23][24][26][27][28]68]. Since there is generally only low, transient, or no VSV viremia in most infected vertebrates (other than experimentally infected rodents) [29,30], infection of biological vectors via ingestion of blood from a VSV-positive host is unlikely to be an important transmission route, albeit still possible [15]. Instead, infection of hematophagous vectors may occur either via co-feeding with already infected insects or via feeding around or in vesicular skin lesions [15,31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation